Bài 1:
a) \(=xy\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(xy-1\right)\)
b) \(=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)=\left(x+y\right)\left(x-y+7\right)\)
c) \(=\left(x+y\right)^2-25=\left(x+y-5\right)\left(x+y+5\right)\)
d) \(=x\left(x-5\right)-3\left(x-5\right)=\left(x-5\right)\left(x-3\right)\)
Bài 2:
a) \(\Rightarrow x^2+x-6=0\)
\(\Rightarrow x\left(x-2\right)+3\left(x-2\right)=0\Rightarrow\left(x-2\right)\left(x+3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\)
b) \(\Rightarrow-x^2+x+20=0\)
\(\Rightarrow-\left[x\left(x-5\right)+4\left(x-5\right)\right]=0\Rightarrow-\left(x-5\right)\left(x+4\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=5\\x=-4\end{matrix}\right.\)
Bài 1:
\(a,=xy\left(x+y\right)-\left(x+y\right)=\left(xy-1\right)\left(x+y\right)\\ b,=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)=\left(x+y\right)\left(x-y+7\right)\\ c,=\left(x+y\right)^2-25=\left(x+y-5\right)\left(x+y+5\right)\\ d,=x^2-3x-5x+15=\left(x-3\right)\left(x-5\right)\)
Bài 2:
\(a,\Leftrightarrow x\left(x+3\right)-2\left(x+3\right)=0\\ \Leftrightarrow\left(x-2\right)\left(x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\\ b,\Leftrightarrow5\left(x+4\right)-x\left(x+4\right)=0\\ \Leftrightarrow\left(5-x\right)\left(x+4\right)=0\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-4\end{matrix}\right.\)